Contribution of agroforestry to climate change mitigation and livelihoods in Western Kenya - Reppin, Saskia; Kuyak, Shem; Neergaard, Andreas de; Oelofse, Myles; Rosenstock, Todd S. (Springer, 2020)
We test the hypothesis that agroforestry improves livelihoods and mitigates climate change in smallholder farming systems simultaneously. Data were collected using household surveys and standard biomass assessment approaches using locally relevant allometric equations. Summary statistics and regression analyses reveal linkages between on-farm carbon stocks and farm- and household characteristics. With an average of 4.07 ± 0.68 Mg C ha-1 and Shannon diversity index of 3.06, farm carbon stocks were significantly associated with farm size (r = 0.453, p\0.05), tree density (r = - 0.58, p = 0.05) and the average size of trees on farm (r = - 0.42, p = 0.05), but not by Shannon diversity index (r = 0.36, p = 0.080), species richness (r = - 0.044, p =0.833) or the number of land use categories (r = - 0.192, p = 0.356). Timber was considered the most important use of on-farm trees before firewood and construction material. The results suggest that gaining self-sufficiency in firewood is the most important benefit with on-farm carbon accumulation. The focus on exotic species for timber production presents a considerable trade-off between livelihood options and environmental goals. Heterogeneity in local environmental conditions over very short distances, less than 12 km, significantly determine livelihood strategies and on-farm carbon stocks. These results ostensibly contradict that carbon storage in smallholder farms is determined by diversity of tree species, suggest that livelihood strategy can equally drive carbon storage and demonstrate the diversity of livelihood and environmental benefits derived from trees on farms.